Effect of charging agents on electrophoretic deposition of coarse titanium particles - Lau, Kok Tee; Charles Sorrell (Australian Ceramic Society, 2013)
The effects of aluminium (III) chloride (AlCl3), polyethyleneimine (PEI), and poly(diallyldimethylammonium chloride) (PDADMAC)] as charging agents on the electrophoretic deposition (EPD) of coarse (≤20 μm) titanium (Ti) particles onto low-carbon steel cathodic substrates were assessed through microstructural evaluation, deposit yield, electrophoretic mobility measurements, and electrolytic corrosion. Apart from the capacity to achieve high bonding strength and yield, PDADMAC resulted in lower electrolytic corrosion of the anode and introduced less anionic contamination than AlCl3 or PEI. The quality of the EPD deposit in terms of its bonding strength and deposit yield depended on the length scale of the charging agents used in addition to the intrinsic nature of the charging agent (ionic functional groups and sites). Minimisation of the PDADMAC addition level and PDADMAC of lower molecular weight are advantageous for surface hardening purposes owing to lower the carbon content introduced into the deposit yield.